Peningkatan Kompetensi Guru-guru SMK melalui Pelatihan Pembuatan Media Pembelajaran Trainer ELektronika Digital Di Kabupaten Pesisir Selatan - Asnil Asnil; Fivia Eliza; Irma Husnaini (Universitas Negeri Padang, 2019)
Increasing teacher competence in managing digital electronics learning in Vocational High Schools must always be managed and improved. This activity can be carried out by training in developing digital engineering learning media, especially regarding logic gates. The trainees work together in teams to complete the given topic, which begins with the design and simulation and then practices in completing assigned instructional media. At the end of the scenario an evaluation of the work carried out and an evaluation of the course of the training activities. From the evaluation results it was found that there was an increase in the competence of vocational teachers in Pesisir Selatan District in mastering learning media, and from the results of the questionnaire analysis, it was concluded that the participants gave a positive response to the implementation of the training.